2010
DOI: 10.1369/jhc.2010.956185
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Labeling of the Inhibin/Activin βC Subunit in Normal Human Placental Tissue and Chorionic Carcinoma Cell Lines

Abstract: (JM) S U M M A R Y Inhibins and activins are important regulators of the female reproductive system. A novel inhibin subunit, named bC, has been identified and demonstrated to be expressed in several human tissues. We demonstrate here that inhibin bC is expressed in human placenta. Expression of the inhibin bC subunit was demonstrated at the protein level by means of immunohistochemical evaluation and at the transcriptional level by an inhibin bC-specific RT-PCR analysis. Expression of inhibin bC was detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Concerning activins B and AB, conflicting studies about their expression in placenta were reported (McCluggage et al, 1998;Petraglia, 1997). The βc and βE subunits were also identified in this organ (Gingelmaier et al, 2011;Weissenbacher et al, 2010).…”
Section: Inhibins and Activinsmentioning
confidence: 99%
“…Concerning activins B and AB, conflicting studies about their expression in placenta were reported (McCluggage et al, 1998;Petraglia, 1997). The βc and βE subunits were also identified in this organ (Gingelmaier et al, 2011;Weissenbacher et al, 2010).…”
Section: Inhibins and Activinsmentioning
confidence: 99%
“…Immunofluorescence analysis was performed as previously described (9,(11)(12)(13)(14)(15)23,25). Briefly, cells grown on glass coverslips were fixed with acetone for 10 min at room temperature and washed twice with PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, two additional β-subunits have been identified in humans, βC and βE (7). Although these novel subunits are synthesised in a wide range of normal and malignant tissues (9)(10)(11)(12)(13)(14)(15), their precise function still remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Since specific antibodies against this inhibin-ßC subunit have been available for just a short period of time, systematic investigations on cervical tissue has not been performed yet. Although the used polyclonal inhibin-ßC antibody is not suitable for immunoblot analysis, it has been successfully used in human placental and endometrial tissue as well as cancer cell lines with a good specificity as confirmed by RT-PCR analysis (12,13,15,30). Therefore, the aim of this study was to analyse the expression of the ßC-subunits in normal and pathological cervical tissue as well as cervical carcinoma cell lines.…”
Section: Immunolabelling Of the Inhibin/activin-ßc Subunit In Normal mentioning
confidence: 99%
“…Additionally, two additional ß-subunits have been identified in humans, determined as ßC and ßE (7). Although these novel subunits are synthesised in wide range of normal and malignant tissues (11)(12)(13)(14)(15), their precise function remains unclear. Moreover, the ßC-isoform is involved in the formation of homodimeric activin C (ßC-ßC) as well as heterodimeric activins AC (ßA-ßC), BC (ßB-ßC), CE (ßC-ßE), as well as inhibin C (•-ßC) have been demonstrated (16,17).…”
Section: Introductionmentioning
confidence: 99%